2019
DOI: 10.1002/joc.6137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the aridity index and its drivers in eight climatic regions in China in recent years and in future projections

Abstract: Intense anthropogenic climate changes are expected to increase atmospheric aridity in the 21st century. The aridity index (AI), defined as the ratio of annual precipitation (Pre) to atmospheric evaporation (potential evapotranspiration [PET]), represents an efficient indicator of climatic changes. However, the variations and underlying drivers of AI values have not been comprehensively compared in different climatic regions. Using the AI calculated on the basis of bias‐corrected precipitation and optimized PET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“… 29 It is found that the whole China has undergone a significant drying trend 43 and the drying trends have shifted gradually from north to south. 44 The significant drying trends have been found on the Bohai Bay area, the Tibet Plateau, 43 , 45 the Loess Plateau, and the Yunnan-Guizhou Plateau. 46 On the contrary, the northwest of China is becoming wetter.…”
Section: Resultsmentioning
confidence: 99%
“… 29 It is found that the whole China has undergone a significant drying trend 43 and the drying trends have shifted gradually from north to south. 44 The significant drying trends have been found on the Bohai Bay area, the Tibet Plateau, 43 , 45 the Loess Plateau, and the Yunnan-Guizhou Plateau. 46 On the contrary, the northwest of China is becoming wetter.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, despite implementing a comprehensive range of quality control measures aimed at achieving objective and sound assessment conclusions, certain uncertainties unavoidably persist. Firstly, the sparsity of meteorological stations in the QTP region [74] poses a challenge as many remote sensing precipitation products rely on ground-based information as input data sources. Moreover, the calibration process of SPPs involves even fewer meteorological stations, resulting in a lower correlation between the SPPs and the observations of weather stations in the research of inter-annual variability within this region.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies highlight the potential for more localized aridity trends, including projection ensembles indicating significant increase in aridity and more frequent and intense droughts in most parts of China (Y. Li et al, 2019;Yao et al, 2020) and India under RCP4.5 and RCP8.5 for the 2020-2100 period (Gupta and Jain, 2018;Bisht et al, 2019;Preethi et al, 2019).…”
Section: Landslidementioning
confidence: 99%